Rapid 3D imaging of the lower airway by MRI in patients with congenital heart disease: A retrospective comparison of delayed volume interpolated breath‐hold examination (VIBE) to turbo spin echo (TSE). (9th September 2016) - Goot, Benjamin H.; Patel, Sonali; Fonseca, Brian
Abstract: Objective: When imaging the lower airway by MRI, the traditional technique turbo spin echo (TSE) results in high quality 2D images, however planning and acquisition times are lengthy. An alternative, delayed volume interpolated breath‐holds examination (VIBE), is a 3D gradient echo technique that produces high spatial resolution imaging of the airway in one breath‐hold. The objective of this study is to retrospectively evaluate the accuracy of lower airway measurements obtained by delayed VIBE when compared to TSE. Design: Patients with congenital heart disease who underwent a cardiac MRI (CMR) that included a delayed VIBE sequence from 5/2008 to 9/2013 were included. Standard TSE imaging was performed and delayed VIBE was acquired 5 min after gadolinium contrast administration. Airway measurements were made on both sequences by two observers in a blinded fashion to the other observer and other technique. Intraclass correlations (ICC) were calculated to assess for agreement between both techniques and the observers. Results: 29 studies met inclusion criteria with a mean patient age of 8.8 years (2 months to 63 years) and mean patient weight of 30.2 kg (3.5‐110). All delayed VIBE and TSE sequences were found to be of diagnostic quality. Mean acquisition time was shorter for the delayed VIBE (13.1 seconds) than TSE (949.9 seconds). Overall there was very good agreement between the delayed VIBE and TSE measurements for both observers (ICC 0.78‐0.94) with the exception of the distal right bronchus (ICC 0.67) The interobserver agreement was also excellent for both TSE (ICC 0.78‐0.96) and VIBE (ICC 0.85‐0.96). Conclusion: Delayed VIBE is rapid and at least as accurate as the alternative TSE imaging for assessment of the lower airway by MRI across a wide spectrum of patients.